Understanding serendipity and its application in the context of information science and technology - Zhou, Xiaosong (2018)
Serendipity is widely experienced in current society, especially in the digital world. According to the Oxford Concise English Dictionary, the term “serendipity” is defined as “the occurrence and development of events by chance in a happy or beneficial way”. This PhD research project aims to understand serendipity in the context of information research, and then attempts to design information technologies which can support the encountering of serendipity in cyberspace.